1997
DOI: 10.1046/j.1365-4362.1997.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromoblastomycosis in India

Abstract: Although chromoblastomycosis is widely distributed in India, many patients remain undiagnosed due to a lack of proper facilities. Treatment is difficult and most patients are not able to afford the drugs prescribed for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 11 publications
2
23
1
Order By: Relevance
“…[3], [4], [5], [6] According to one report, Madagascar represents the most important focus of this fungal disease. [7] Brazil is another country reporting large number of cases. [3], [4], [5] In most of these reports, chromoblastomycosis is seen to be a disease of rural male agriculturists and the commonest etiological agent is F. pedrosoi.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…[3], [4], [5], [6] According to one report, Madagascar represents the most important focus of this fungal disease. [7] Brazil is another country reporting large number of cases. [3], [4], [5] In most of these reports, chromoblastomycosis is seen to be a disease of rural male agriculturists and the commonest etiological agent is F. pedrosoi.…”
Section: Treatmentmentioning
confidence: 99%
“…Rajendran et al in 1997 reviewed 30 cases till then from all over India and reported 4 new cases including 2 cases from Jammu and Kashmir and Bihar. [7] Sharma et al in 1999 also reviewed the Indian scenario and reported four more cases. [8] Kumar et al reported two cases in 2000 and Sharma A reported four cases from Assam in 2010.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few sporadic cases have been reported from eastern India [1]. It is usually an occupational disease following traumatic implantation of saprophytic fungi, mainly affecting individual in tropical and temperate regions [2].…”
Section: Introductionmentioning
confidence: 99%
“…Cases have been documented from several states of India (1)(2)(3)(4)(5). The characteristic lesions are warty papules, verrucous plaques or solid nodules developing in the skin at the site of traumatic implantation of the fungus, usually at an extremity (6).…”
Section: Introductionmentioning
confidence: 99%